Caravans in the Steppes of Central Eurasia: caravan routes - Tairov Aleksandr D. (Поволжская археология, 2025)
The research aims to reconstruct caravan routes through the steppes of Central Eurasia. These caravan routes connect Central Asia with the forest and forest-steppe regions of the Trans-Urals and Western Siberia. Reconstruction of the main caravan routes is based on synthesis of archaeological, written, cartographic sources and toponymic and geographic data. In this case, it is necessary to consider two constant factors: “natural corridors” through large natural barriers and the characteristics of the pack animals that were used to transport goods. The initial basis for these reconstructions can be cartographic materials from the XVIII – early XX centuries. The result of the work was the reconstruction of the main caravan routes through the steppes of Central Eurasia, which could have been used in ancient times and the Middle Ages.